2023
DOI: 10.3847/2041-8213/acc393
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Isotopic Composition of Hydrous Minerals in Asteroid Ryugu

Abstract: Rock fragments of the Cb-type asteroid Ryugu returned to Earth by the JAXA Hayabusa2 mission share mineralogical, chemical, and isotopic properties with the Ivuna-type (CI) carbonaceous chondrites. Similar to CI chondrites, these fragments underwent extensive aqueous alteration and consist predominantly of hydrous minerals likely formed in the presence of liquid water on the Ryugu parent asteroid. Here we present an in situ analytical survey performed by secondary ion mass spectrometry from which we have estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…It is a factor of 3 lower than the ratio for water in 67P/CG but fully compatible with the D/H ratio of hydrous minerals in CI chondrites (Piani et al. 2021 , 2023 ). However, as pointed out by Nittler et al.…”
Section: Isotopic Compositionssupporting
confidence: 75%
See 3 more Smart Citations
“…It is a factor of 3 lower than the ratio for water in 67P/CG but fully compatible with the D/H ratio of hydrous minerals in CI chondrites (Piani et al. 2021 , 2023 ). However, as pointed out by Nittler et al.…”
Section: Isotopic Compositionssupporting
confidence: 75%
“…( 2023 ) inferred a D/H ratio of for water in Ryugu, which is slightly higher than that of Piani et al. ( 2023 ) and that of CI chondrites. These authors used an experimental approach that minimizes the effect of H contamination from organics interspersed with silicates.…”
Section: Isotopic Compositionsmentioning
confidence: 72%
See 2 more Smart Citations
“…The bulk elemental and isotopic abundances, and organic carbon contents (1.8∼4.0 wt.%) were in agreement with those of CI chondrites [19,[23][24][25][26]. The O-Cr isotopic compositions [19,23,27] indicated that Ryugu sampled the least thermally processed PSN material.…”
Section: The Nature Of Ryugu Particlessupporting
confidence: 69%